Anticancer, Free Radicals, and Digestive Enzyme Inhibitory Activities of Rubus sanctus Schreb Root Four Solvent Fractions. (17th June 2021) - Jaradat, Nidal; Dwikat, Majdi; Amer, Johnny; Hawash, Mohammed; Hussein, Fatima; Qneibi, Mohammad; Issa, Linda; Asab, Jalal Abu; Hallak, Haya; Arar, Diana Nael; Masri, Hala Zidan; Obeid, Khalil; et al.
Abstract : Background . Humankind used herbal products as a source of medicines since they understood their therapeutic benefits from ancient times. Therefore, the current research aimed to determine the anticancer, antioxidant, and metabolic enzyme inhibitory activities of Rubus sanctus (RS) root four solvent fractions for the first time. Methods . The antioxidant, antilipase, and anti- α -amylase potentials of (RS) four solvent fractions were evaluated using standard biomedical assays. Moreover, the DNA cell cycle of liver cancer was assessed using a propidium iodide (PI) assay. At the same time, the apoptosis activity was estimated utilizing flow the cytometry method. Results . The methanol and acetone (RS) fractions showed the highest antioxidant activity with IC50 values of 0.078 ± 0.22 and 0.67 ± 0.25  μ g/ml, respectively, compared with Trolox, which has an antioxidant IC50 value of 2.039 ± 0.52  μ g/ml. Moreover, the methanol (RS) fraction has the highest anti- α -amylase activity with an IC50 value of 20.12 ± 0.34  μ g/ml compared with acarbose, which has an IC50 value of 6.565 ± 0.3  μ g/ml. Also, the acetone (RS) fraction revealed the highest antilipase activity with an IC50 value of 6.03 ± 1.23  μ g/ml compared with the positive control orlistat which has an IC50 value of 0.39 ± 0.45  μ g/ml. The aqueous, methanol, acetone, and hexane fractions of the (RS) roots decreased the secretion of the α -fetoprotein in the liver cancer cells. The acetone fraction was the most potent α -fetoprotein inhibitor with an average of 237 ± 12.5% compared with the average of the untreated cells, which was 4066.6 ± 202%. The hexane fraction was the most effective in diminishing apoptosis with an average of 14.5 ± 1.6%, compared with 49% ± 2 untreated cells' average. In inhibiting cell cycle progression, it was recognized that methanol fraction seems to be the most powerful amplifier of the (RS) effect, as it increased the proportion of the cells with an average of 24.5 ± 2.2%, compared with 7.4 ± 1.8% in the doxorubicin (DOX). Data indicated a decrease in cell proliferation rate by prolonging the G2-M phase and thus slowing cancer progression. Our results suggest that (RS) roots four solvent fractions have potential anticancer activity. Conclusion . The (RS) roots four solvent fractions have potential anticancer, antioxidant, antilipase, and α -amylase inhibitory activities. It could be a promising source for applications in the functional food, nutraceutical, and pharmaceutical industries.